If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 4x + 3 Reorder the terms: -1 + 7x = 4x + 3 Reorder the terms: -1 + 7x = 3 + 4x Solving -1 + 7x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + 7x + -4x = 3 + 4x + -4x Combine like terms: 7x + -4x = 3x -1 + 3x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + 3x = 3 + 0 -1 + 3x = 3 Add '1' to each side of the equation. -1 + 1 + 3x = 3 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = 3 + 1 3x = 3 + 1 Combine like terms: 3 + 1 = 4 3x = 4 Divide each side by '3'. x = 1.333333333 Simplifying x = 1.333333333
| 0.4x+0.2(30)=0.3(x+30) | | -5x-7(-3x+9)=113 | | 9(z-3)=2(z+1) | | 4x+23=12x-76 | | 3y^2-3y-22=0 | | 5t-t-7=3t-5 | | 0.5x+0.4(30)=0.3(x+30) | | 7m-5=2m-20 | | 11x-31=6x+14 | | 25c^2-70c+49=0 | | 8k+5=4k+13 | | -9y-10=-5y+14 | | 1.5x+1.3=.25x-1.16 | | l+41/2=5 | | 2x+79=8x+3 | | -1+5(4n+3)=2(4n-5)+6 | | 2p-14=2p+10 | | 6X=7X-1 | | 7=(10+x)/2 | | -3=(-3+x)/2 | | 3*2-2(11-8)*2=36x | | 4a-4=a+5 | | 11=(12-x)/2 | | 6+9(n-1)=3(-3n-4)-6 | | 4=(4-x)/2 | | 2x+7y-9z= | | 2=(6+x)/2 | | a+3b+80+90=100 | | -5w-14=-7w | | 8(x-1)+36=-3(2x+5) | | 1=(-3+X)/2 | | 7(x^2+9)=35 |